Exploitation and distribution of the artisanal shrimp catch in the Lagunar Huave System, Oaxaca, Mexico - Cervantes-Hernández, Pedro; Gallardo-Berumen, Ma. Isabel; Serrano-Guzmán, Saúl J. (Revista Ciencias Marinas y Costeras, 2012)
In the Huave Lagoon System, the artisanal exploitation and distribution of shrimp were affected by the loss of hydrological quality (surface temperature, salinity, dissolved oxygenate and turbidity) and mangrove cover. The best hydrological conditions with extensive mangrove areas were observed in the Oriental and Occidental Lagoons, where 97% of artisanal shrimp catches was obtained. The worst hydrological conditions with little mangrove area were recorded within (0.35%) and in the entrance (0.85%) of the Mar Tileme Lagoon, where artisanal shrimp catches were low, recording a natural mortality rate of 0.80 per month. The period analyzed was from 1999 to 2007; however, according to the literature, the marine recruitment of juvenile shrimp in this lagoon system began to decline in the Gulf of Tehuantepec during 1980s. Fishing pressure was modified by the prevailing environmental conditions in each lagoon section. This pressure was “very low” in the Mar Tileme Lagoon, “high” in the Oriental and Occidental Lagoons, and “low” in the Inferior Lagoon.